Why motivating people doesn't work ... and what does : more breakthroughs for leading, energizing, and engaging - Fowler, Susan, 1951- (Berrett-Koehler Publishers, Inc., 2023)
"You can't motivate people, but you can help people learn to motivate themselves. This second edition includes new material on inspiring self-motivation in remote workers and a distributed workforce. What if the answer to motivating people is to stop trying to motivate them? Leadership researcher, consultant, and coach Susan Fowler says that overtly trying to motivate your employees can be frustrating for everyone involved and doesn't work in the long term. You can't force people to be motivated-but you can help them find the inner commitment that increases productivity and engagement and gives them a profound sense of purpose and fulfillment. The second edition of this bestseller includes a new chapter on remote and hybrid work as well as updated content on postpandemic management, DEIJ initiatives, and the Great Resignation. Fowler uses the Self-Determination Theory to show the positive effects of optimal motivation on people's vitality, productivity, and creativity and lays out a tested model and course of action for leaders. In addition, she includes compelling examples and anecdotal evidence from applying her techniques in organizations and with individuals worldwide. Fowler shows leaders how to get out of the way and encourage their people to self-motivate and foster personal excellence"--